Computational study of chalcogenide based solar energy materials - Dongho Nguimdo, Guy Moise (My University, 2016)
Amongst the major technological challenges of the twenty rst century is the harvesting of renewable energy sources. We studied the solar cell performance of the ternary compounds AgAlX2 (X = S, Se and Te) and AgInS2 as promising materials for meeting this challenge. Structural, electronic and optical properties of the compounds were investigated by means of the density functional theory and many body perturbation theory. Using cohesive energy and enthalpy, we found that among six potential phases of AgAlX2 and AgInS2, the chalcopyrite and the orthorhombic structures were very competitive as zero pressure phases. We predicted a low pressure-induced phase transition from the chalcopyrite phase to a rhombohedral phase. For the chalcopyrite phase, we found that the tetragonal distortion and anion displacement were the cause of the crystal eld splitting. The bandgaps from the general gradient approximation PBEsol were underestimated when compared to experiment and accurate bandgaps were obtained from the hybrid functioanl HSE06, the meta-general gradient approximation MBJ and GW approximation. Optical absorption from the Bethe-Selpeter equation indicated the presence of bound exciton in AgAlX2. We estimated the solar cell performance of the compounds using the Shockley and Queisser model and the spectroscopy limited maximum e ciency approach. We found that apart from AgAlS2, the estimated theoretical e ciency of the other compounds was greater that 13 %.
A thesis submitted to the Faculty of Science, in fulfilment of the requirements for the degree of Doctor of Philosophy. University of the Witwatersrand, Johannesburg May 23, 2016
Keywords: Chalcogenides; Solar energy--Materials